STUDENT ATTITUDES TOWARD THE USE OF CHATBOTS IN CUSTOMER SERVICE - Lupa-Wójcik, Iwona (Zeszyty Naukowe SGGW, Polityki Europejskie, Finanse i Marketing, 2019)
The article addresses an important and current problem related to the use of chatbots in customer service, according to students. The aim of the research was to recognize the attitude of respondents to chatbots in the context of customer service and to determine the development prospects for their use in this area. The research examined the recognizability of chatbots among respondents, the frequency of contact between respondents and chatbots, as well as the impression (feeling) of respondents using chatbots. As a research method, student survey was used. Research has shown that chatbots are still a new tool for respondents, however they have great potential in customer service, as they are user-friendly and are very useful in the area of customer service. Research has shown that the role of chatbots in this area should increase. This can have a good effect on the image of the brand / company.